RAPE TRAUMA SYNDROME REPRESENTATION AS SEEN IN THE WAY I USED TO BE NOVEL BY AMBER SMITH - Delfira Rizkiana; Muhammad Fithratullah (Linguistics and Literature Students' Journal, 2022)
This research focuses on the discussion of the Rape Trauma Syndrome (RTS) representation in the novel entitled The Way I Used to Be that was written by Amber Smith. The synopsis of the novel told about the suffering of the main character, fourteen year’s old Eden, who changed after her older brother’s best friend raped her one night on the Christmas break. By looking at the synopsis of the novel, the writer aims to see the way the novel represented the existence of RTS through its main character, Eden, who at that time experienced sexual assault. To conduct the research, the writer uses a descriptive qualitative methods to describe and explain the issue of RTS inside the novel. Therefore, to support the analysis and explanation, the writer uses the theory of psychological approach as well as the Rape Trauma Syndrome (RTS) theory that explains the signs and phases of RTS. By that, the writer is able to see, reveal, and explain the way the novel represented the existence of the RTS through the main character. After doing the analysis, the writer found that Eden in the novel, suffered from RTS due to her trauma of rape. It was because Edy was seen fulfilled all of the symptoms of RTS. She also fulfilled all the phases of RTS which are acute phase, outward adjustment phase, and resolution phase. It was all seen through her behavior and attitudes throughout the novel.Keywords: Main character, psychological approach, rape trauma syndrome, the way I used to be